CONTAGIOUS EFFECTS OF OIL PRICES ON ASIAN STOCK MARKETS’ BEHAVIOUR - Jok-Tong Wan; Evan Lau; Rayenda Khresna Brahmana (Journal of Indonesian Economy and Business (JIEB), 2016)
The main objective of this study is to examine the stock markets’ shock due to the effect of the price of oil in the East Asia Region. Particularly, this study examines if there is stock market interdependence during global oil price shocks (sudden changes) for a sample of five total oil importers (the Philippines, Hong Kong SAR, Taiwan, South Korea, and Japan), four net oil importers (Indonesia, Singapore, Thailand, and China), and one net oil exporter (Malaysia) between 1999 and 2014. From the result, an oil price change is collectively found to have a small but significant positive impact on the stock markets, in particular where a sudden decrease in oil prices tends to cause a stock market downturn and volatility. The world economy’s spending, financial investments in oil futures and foreign investment by oil rich nations are some underlying motives for inducing this oil-stock positive relation. The same direction of time-varying conditional correlations is found across East Asian stock markets during negative oil price shocks. The integration among East Asian stock markets is inducing the oil shock contagion to be transmitted from direct oil-affected countries (South Korea, Hong Kong, and Singapore) to non-direct oil affected countries’ (Japan and Taiwan) stock markets. In spite of a long practiced ASEAN+3 macroeconomics surveillance process and Early Warning System (EWS) which can be customized for stock markets to prevent or detect the oil risk, hedging against initial oil-affected stock markets and a stronger influence by the East Asian countries in the global world of oil and capital investment are strongly suggested.Keywords: oil price; capital market integration; stock market behaviour